On the use of penalty approach for design and analysis of univariate alarm systems. (September 2018) - Taheri-Kalani, J.; Latif-Shabgahi, G.; Alyari Shooredeli, M.
Highlights: In this paper, a generalized method for designing of delay timers is introduced based on a new concept named "penalty". It provides more flexibility in alarm design. The paper formulated indices, FAR and MAR for various penalties. Also, to calculate AAD, another index named MTTA is introduced. In the sense of performance, it has been proved that indices FAR, MAR and AAD in penalty scenario give better results compared with those of the reset scenarios with 2 ≤ i < n - 1 . Abstract: Alarm systems indicate abnormal conditions of the underlined plant equipment enabling operators to take corrective actions, and bring the equipment back to its normal condition. This paper presents a new approach for designing a generalized delay timer based on the penalty scenario and Markov chain schemes. The penalty approach is an extension for the well-known "n-sample on/off delay timer" approach in designing alarm systems. Three performance indices named, False Alarm Rate (FAR), Missed Alarm Rate (MAR) and Average Alarm Delay (AAD) are derived for the proposed penalty approach using Markov theory. Also, a new index named "Mean Time to Alarm (MTTA)" is introduced to analyze the underline alarm system, and to compute AAD. Finally, the effectiveness of the proposed method is investigated and compared with that of the other methods through a case study.